2007
DOI: 10.1128/mcb.00363-07
|View full text |Cite
|
Sign up to set email alerts
|

Wobble Splicing Reveals the Role of the Branch Point Sequence-to-NAGNAG Region in 3′ Tandem Splice Site Selection

Abstract: Alternative splicing involving the 3 tandem splice site NAGNAG sequence may play a role in the structurefunction diversity of proteins. However, how 3 tandem splice site utilization is determined is not well understood. We previously demonstrated that 3 NAGNAG-based wobble splicing occurs mostly in a tissueand developmental stage-independent manner. Bioinformatic analysis reveals that the nucleotide preceding the AG dinucleotide may influence 3 splice site utilization; this is also supported by an in vivo spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
(47 reference statements)
6
28
0
3
Order By: Relevance
“…1B). This finding was consistent with a report by Tsai et al (2007), which demonstrated that the "N" nucleotide preceding AG plays a critical role in the 3' wobble splicing and the ratio (up to 87.9%) of distal AG selection in NAGNAG tandem motif. In addition, the KIT receptor is characterized by the presence of five immunoglobulin-like domains in its extracellular portion (Liu et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…1B). This finding was consistent with a report by Tsai et al (2007), which demonstrated that the "N" nucleotide preceding AG plays a critical role in the 3' wobble splicing and the ratio (up to 87.9%) of distal AG selection in NAGNAG tandem motif. In addition, the KIT receptor is characterized by the presence of five immunoglobulin-like domains in its extracellular portion (Liu et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…At some minimal distance, spatial constraints of the spliceosome will likely dictate limits on the branchpoints and splice sites used in the excision of the intron. The contribution to 3 ′ splice site choice that the physical distance from the alternative 3 ′ splice site to the branchpoint makes has been explored in other organisms (Akerman and MandelGutfreund 2006;Tsai et al 2007Tsai et al , 2010Bradley et al 2012). Expression analysis of a PTB minigene with 4-nt or 7-nt insertions between the branchpoint and tandem acceptor set caused an increase in splicing to the proximal site, suggesting that the choice of branchpoint may influence the choice of 3 ′ splice site at NAGNAGs (Tsai et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAGNAG acceptors are very common in genes from a variety of organisms from land plants to humans (Hiller et al 2004;Schindler et al 2008). Although the use of the alternative NAGNAG sites (known as 39 splice junction wobbling) has been argued to be stochastic (Chern et al 2006;Sinha et al 2009), evidence exists for functional effects of the single amino acid differences generated by the use of the alternative acceptors (Tsai et al 2008) and for arrangements of regulatory sequences at these regions (Akerman and Mandel-Gutfreund 2006;Tsai et al 2007). …”
Section: Splicing Defect In Alps Mutationmentioning
confidence: 99%